Pneumoconiosis among miners in coal mines - Bojan Joksimović; Biljana Mijović; Biljana Čančar; Milena Božinović; Zlatko Maksimović; Slobodan Stanić; Đorđe Jevtić (Биомедицинска истраживања, 2021)
Pneumoconiosis of workers in brown coal mines is an occupational disease, a global public health problem and a serious disease of the lung parenchyma. If it is not prevented, it leads to irreversible changes in the lungs with complications. The disorder occurs after prolonged exposure to coal dust containing high concentration of free crystalline silica. Data in literature regarding its health impact on people working in coal mines are relatively scarce. Recently, there has been an increase in miners' pneumoconiosis, which requires a stricter policy to protect workers in the mines. There are two classical types of CWP: simple and complicated. The main diagnostic method of CWP is based on a specific X-ray finding, and the auxiliary method of choice is spirometry. The pathophysiological mechanism of CWP formation is not fully known, although it has been shown that damage to the lung parenchyma goes through three phases caused by effect of lung cells exposure to coal dust. Studies show that cytokines play an important role in inflammation and the immune response as mediators of toxic and pathogenic effects in CWP. A link between exposure to coal dust in brown coal mines and the development of CWP has also been demonstrated, with a consequent reduction in the physical and psychological quality of life of workers in the mines.
Keywords: pneumoconiosis; coal dust; miners